Latitude and lake size are important predictors of over‐lake atmospheric stability. Issue 17 (5th September 2017) - Woolway, R. Iestyn; Verburg, Piet; Merchant, Christopher J.; Lenters, John D.; Hamilton, David P.; Brookes, Justin; Kelly, Sean; Hook, Simon; Laas, Alo; Pierson, Don; Rimmer, Alon; Rusak, James A.; et al.
Abstract: Turbulent fluxes across the air‐water interface are integral to determining lake heat budgets, evaporation, and carbon emissions from lakes. The stability of the atmospheric boundary layer (ABL) influences the exchange of turbulent energy. We explore the differences in over‐lake ABL stability using data from 39 globally distributed lakes. The frequency of unstable ABL conditions varied between lakes from 71 to 100% of the time, with average air temperatures typically several degrees below the average lake surface temperature. This difference increased with decreasing latitude, resulting in a more frequently unstable ABL and a more efficient energy transfer to and from the atmosphere, toward the tropics. In addition, during summer the frequency of unstable ABL conditions decreased with increasing lake surface area. The dependency of ABL stability on latitude and lake size has implications for heat loss and carbon fluxes from lakes, the hydrologic cycle, and climate change effects. Key Points: Atmospheric boundary layer stability above lakes varies predictably across temporal and spatial scales The atmospheric boundary layer above lakes is more often unstable toward the tropics annually and above smaller lakes during summer The effects of latitude and lake size on lake‐atmosphere interactions have implications for heat loss from lakes and the hydrologic cycle